Three Vessel Coronary Cameral Fistulae Associated with New Onset Atrial Fibrillation and Angina Pectoris - Murat Yuksel; Abdulkadir Yildiz; Mustafa Oylumlu; Nihat Polat; Halit Acet; Necdet Ozaydogdu (Case Reports in Vascular Medicine)
Coronary cameral fistulas are abnormal communications between a coronary artery and a heart chamber or a great vessel which are reported in less than 0.1% of patients undergoing diagnostic coronary angiography. All three major coronary arteries are even less frequently involved in fistula formation as it is the case in our patient. A 68-year-old woman was admitted to cardiology clinic with complaints of exertional dyspnea and angina for two years and a new onset palpitation. Standard 12-lead electrocardiogram revealed atrial fibrillation (AF) with a ventricular rate of 114 beat/minute and accompanying T wave abnormalities and minimal ST-depression on lateral derivations. Transthoracic echocardiographic examination was normal except for diastolic dysfunction, minimally mitral regurgitation, and mild to moderate enlargement of the left atrium. Sinus rhythm was achieved by medical cardioversion with amiodarone infusion. Coronary angiography revealed diffuse and multiple coronary-left ventricle fistulas originating from the distal segments of both left and right coronary arterial systems without any stenosis in epicardial coronary arteries. The patient’s symptoms resolved almost completely with medical therapy. High volume shunts via coronary artery to left ventricular microfistulas may lead to increased volume overload and subsequent increase in end-diastolic pressure of the left ventricle and may cause left atrial enlargement.